Vitamin D Status Is Associated With Arterial Stiffness and Vascular Dysfunction in Healthy Humans - Al Mheid, Ibhar (2011)
OBJECTIVES: The primary objective of this study was to elucidate mechanisms underlying the link between vitamin D status and cardiovascular disease by exploring the relationship between 25-hydroxyvitamin D (25-OH D), an established marker of vitamin D status, and vascular function in healthy adults. BACKGROUND: Mechanisms underlying vitamin D deficiency-mediated increased risk of cardiovascular disease remain unknown. Vitamin D influences endothelial and smooth muscle cell function, mediates inflammation, and modulates the renin-angiotensin-aldosterone axis. We investigated the relationship between vitamin D status and vascular function in humans, with the hypothesis that vitamin D insufficiency will be associated with increased arterial stiffness and abnormal vascular function. METHODS: We measured serum 25-OH D in 554 subjects. Endothelial function was assessed as brachial artery flow-mediated dilation, and microvascular function was assessed as digital reactive hyperemia index. Carotid-femoral pulse wave velocity and radial tonometry-derived central augmentation index and subendocardial viability ratio were measured to assess arterial stiffness. RESULTS: Mean 25-OH D was 31.8 ± 14 ng/ml. After adjustment for age, sex, race, body mass index, total cholesterol, low-density lipoprotein, triglycerides, C-reactive protein, and medication use, 25-OH D remained independently associated with flow-mediated vasodilation (β = 0.1, p = 0.03), reactive hyperemia index (β = 0.23, p < 0.001), pulse wave velocity (β = −0.09, p = 0.04), augmentation index (β = −0.11, p = 0.03), and subendocardial viability ratio (β = 0.18, p = 0.001). In 42 subjects with vitamin D insufficiency, normalization of 25-OH D at 6 months was associated with increases in reactive hyperemia index (0.38 ± 0.14, p = 0.009) and subendocardial viability ratio (7.7 ± 3.1, p = 0.04), and a decrease in mean arterial pressure (4.6 ± 2.3 mm Hg, p = 0.02). CONCLUSIONS: Vitamin D insufficiency is associated with increased arterial stiffness and endothelial dysfunction in the conductance and resistance blood vessels in humans, irrespective of traditional risk burden. Our findings provide impetus for larger trials to assess the effects of vitamin D therapy in cardiovascular disease.